ANALISIS STRATEGI PENGEMBANGAN AGROFORESTRI BERDASARKAN RANCANGAN TEKNIS IUPHKm DI DUSUN MELINANI, DESA MANUSELA, KABUPATEN MALUKU TENGAH - Nicolas E. Patoding; John M. Matinahoru; Gun Mardiatmoko (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2018)
Agroforestry is a land use system that aims to sustain or increase total yields sustainably. Community Forest Utilization Permit (IUPHKm) is a business permit granted to local community groups to utilize forests in protected forest areas and / or production forest areas. HKm management for the community in the Melinani sub-district was carried out based on the technical design of agroforestry made by BPSKL in the Maluku and Papua regions. The research objectives are: (1) Knowing the economic, social and cultural and ecological characteristics of the Melinani community in utilizing Hkm; (2) Determine strategies and priorities for developing agroforestry systems and (3) Analyze the factors that determine the effectiveness of farmers' work. Multiple regression analysis is used in this research. For the determination of agroforestry development strategies used SWOT analysis and priority setting that must be carried out using the QSPM method. The results of the regression analysis indicate that the level of education and distance from residence have an impact on the development of agroforestry. The SWOT analysis is in the quadrant I. This means that even though the management of agroforestry development is under threat, it can be used to exploit opportunities. The results of QSPM calculations are 4 alternative agrofoestry management strategies in HKm. The technical design of agroforestry is still focused on agriculture and plantation crops, not yet combined with forestry plants, so the strata of the plant have not been well formed.